Functions of Melatonin during Postharvest of Horticultural Crops - Aghdam, M. S.; Mukherjee, S.; Flores, F. B.; Arnao, M. B.; Luo, Z.; Corpas, F. J.
Melatonin, a tryptophan-derived molecule, is endogenously generated in animal, plant, fungal and prokaryotic cells. Given its antioxidant properties, is involved in a myriad of signalling functions associated with various aspects of plant growth and development. In higher plants, melatonin interacts with plant regulators such as phytohormones, as well as reactive oxygen and nitrogen species (ROS/RNS)including hydrogen peroxide (H2O2), nitric oxide (NO)and hydrogen sulfide (H2S). It shows great potential as a biotechnological tool to alleviate biotic and abiotic stress, to delay senescence and to conserve the sensory and nutritional quality of postharvest horticultural products which are of considerable economic importance worldwide. This review provides a comprehensive overview of the biochemistry of melatonin, whose endogenous induction and exogenous application can play an important biotechnological role in enhancing the marketability and hence earnings from postharvest horticultural crops.
Keywords: HORTICULTURAL CROPS; LOW TEMPERATURE STORAGE; MELATONIN; POSTHARVEST; RNS; ROS SCAVENGING SYSTEMS; SENSORY AND NUTRITIONAL QUALITY